What Every Engineer Should Know About the Internet of Things - DeFranco, Joanna F.; Kassab, Mohamad (What Every Engineer Should Know, 2022)
Internet of Things (IoT) products and cyber-physical systems (CPS) are being utilized in almost every discipline. In addition, a significant increase in spending on design, development, and deployment of IoT applications and analytics within every domain, from our homes, schools, healthcare, government, and industry will continue. This practical text provides an introduction to IoT that can be understood by every engineering discipline and discusses detailed applications of IoT. Developed to help engineers navigate this increasingly important and cross-disciplinary topic, this work: Offers research-based examples and case studies to facilitate the understanding of each IoT primitive Highlights IoT’s connection to several domains and technologies. Provides an understanding of benefits and challenges of IoT and its importance to a variety of domains. Written to be accessible to nonexperts in the subject, this work communicates the importance of this technology and how it can support and challenge all interrelated actors as well as all involved assets across many areas.